Assessment framework for water-suitable planting patterns of economic tree species in arid areas - Chao Xu; Wei Kong; Dongmei Zhao; Ting Bai; Fei Gao; Xiaobo Luan; Shikun Sun (Agricultural Water Management)
Appropriate forest restoration is of great significance in arid regions. However, it is necessary to balance soil moisture utilization to maintain the health of the ecosystem. The northern Shaanxi region of the Loess Plateau has undergone large-scale afforestation, primarily focused on fruit tree planting. Although it is a favorable production area for apples, unreasonable planting patterns have exacerbated soil moisture consumption, leading to a contradiction between orchard expansion and water scarcity. Therefore, this study selects apple orchards in this region as the research subject. By integrating the calibrated WinEPIC model and MaxEnt model, the study evaluates water-suitable planting patterns for orchards, including suitable planting years, planting density, theoretical coverage, and the evolution of suitable growth areas under future climate scenarios. The main conclusions are as follows: (1) Orchard yield and water productivity show a parabolic increasing trend with planting density; (2) The suitable planting density for representative orchards varies between 611 and 1099 trees/hm², and the theoretical coverage gradually decreases from south to north; (3) Under future climate scenarios, the distribution range of suitable growth areas becomes more concentrated, with the centroid of suitable areas shifting northward. This study is of great significance for guiding the sustainable development of the apple industry in northern Shaanxi. At the same time, it also provides valuable references and examples for forest restoration and water-suitable planting of tree species in other similar regions.